Implementation of Special Autonomy Policy in Papua Province - Sri Sundari (PT Publikasiku Academic Solution, 2023)
A phenomenon that is made object research is the implementation of the special autonomy policy in increasing the Human Development Index (IPM) in Papua Province. The research objectives are (1) to Analyze the Implementation of special autonomy policy in increasing HDI; (2) to Analyze the constraints of implementing special autonomy policy in increasing HDI; (3) to Develop a strategy for implementing special autonomy policy in increasing HDI. This research uses a qualitative research approach. Research informants as many as 4 people determined by snowball technique. Secondary data collection using literature study; primary data collection using interview and observation techniques. Data analysis used descriptive analysis which was developed by triangulation analysis of observers. The results of the study are as follows: The implementation of the special autonomy policy in increasing the Human Development Index in Papua Province has not been optimal, as theoretically shows limitations of policy implementation in fulfilling the interests of the parties affected; types of benefits received; expected rate of change; decision-making position; program executor; and resource commitment; as well as weakness in anticipation the strength of the actors involved; the interests of the actors involved; the strategy of the actors involved; regime and institutional characteristics; obedience; and responsiveness. Practically, the implementation of the special autonomy policy in increasing the Human Development Index in Papua Province is not optimal, because the data shows that the Human Development Index for Papua is still low. Obstacles to the implementation of the special autonomy policy in increasing HDI include structural constraints, cultural constraints, and conditional constraints. The strategic model that can be developed from discussing the implementation of the special autonomy policy in increasing the HDI in Papua Province is ASOCA Special Autonomy Strategy Model